School-on-the-air on Climate-Smart Agriculture (SOA-CSA) in Cagayan Valley (The Philippines) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In August 2018, more than 6,000 of the 10,078 farmers who enrolled in SOA-CSA project graduated in the program. For this year, a national SOA will be implemented targeting 600,000 farmers under the Rice Competitiveness Enhancement Program, and eventually, 2M farmers in 2022.